A Deep Hybrid Model for Human-Computer Interaction Using Dynamic Hand Gesture Recognition - Ramalingam, Brindha; Angappan, Geetha (Computer Assisted Methods in Engineering and Science, 2023)
Dynamic hand gestures attract great interest and are utilized in different fields. Among these, man-machine interaction is an interesting area that makes use of the hand to provide a natural way of interaction between them. A dynamic hand gesture recognition system is proposed in this paper, which helps to perform control operations in applications such as music players, video games, etc. The key motivation of this research is to provide a simple, touch-free system for effortless and faster human-computer interaction (HCI). As this proposed model employs dynamic hand gestures, HCI is achieved by building a model with a convolutional neural network (CNN) and long short-term memory (LSTM) networks. CNN helps in extracting important features from the images and LSTM helps to extract the motion information between the frames. Various models are constructed by differing the LSTM and CNN layers. The proposed system is tested on an existing EgoGesture dataset that has several classes of gestures from which the dynamic gestures are utilized. This dataset is used as it has more data with a complex background, actions performed with varying speeds, lighting conditions, etc. This proposed hand gesture recognition system attained an accuracy of 93%, which is better than other existing systems subject to certain limitations.